Treatment with nusinersen in a girl with spinal muscular atrophy type 1 - Loboda, Tanja (Zdravniški vestnik, 2020)
We report the case of a girl with spinal muscular atrophy (SMA) type 1, who is the first patient with SMA in Slovenia treated with nusinersen, the first disease modifying therapy available for these patients. SMA is an autosomal recessive neuromuscular disorder characterized by muscle weakness, atrophy and paralysis due to the degeneration of the anterior horn cells, leading to premature death, most commonly due to respiratory infections. Nusinersen, an antisense oligonucleotide, was clinically approved based on clinical trials showing dramatic improvement in the natural course of infantile-onset SMA. After the genetic confirmation of SMA, our girl was the first child in Slovenia to receive nusinersen, which was provided through an expanded access programme. She received intrathecal applications of nusinersen according to the protocol. No serious adverse events were observed. Assessment of her motor skills was performed using The Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP - INTEND) be - fore the beginning of treatment and after completing the first 7 applications of nusinersen. She scored 21/64 points before the introduction of treatment and 32/64 after the completion of treatment. In conclusion, nusinersen improved the CHOP - INTEND motor function score and has been effective in delaying the expected natural course of SMA in our patient.
Keywords: child; naravni potek bolezni; natural course of the disease; otrok; spinal muscular atrophy; spinalna mišična atrofija